DAMPAK KERAGAMAN PRODUK TERHADAP KEPUASAN PELANGGAN RAMAYANA DEPARTEMEN STORE - Hadita, Hadita (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this study is to determine the effect of product price diversity, which consists of product quality diversity, product type diversity, product display diversity to customer satisfaction. The sampling technique uses accidental sampling with 90 respondents in the Tebat branch of Ramayana, and data collection techniques using multiple linear regression. The results of the analysis show the variable of product quality diversity and product display variables have a positive and significant influence on customer satisfaction in the Ramayana branch of Tebet. While the variable price of product prices and the diversity of product types have no effect on customer satisfaction in the Ramayana Depart. Store Tebet branch. Keywords: product price diversity, product quality diversity, product type diversity, product display diversity, customer satisfaction